A novel classification for coronal remaining dentine thickness in carious teeth - Maqbool, Manahil (2025)
Dental caries is a prevalent issue impacting a significant portion of the population. The part of coronal dentine that remains following a carious attack is referred to as the remaining dentine thickness (RDT). The amount of RDT left after caries significantly influences diagnosis and treatment planning. This study aimed to introduce a novel classification that categorises coronal RDT based on its decreasing thickness and information on its related factors. A comprehensive study design incorporating a systematic review (SR), an in vitro experiment, and a modified Delphi technique was employed. Articles measuring coronal RDT were screened for the SR. For the in vitro experiment, human extracted carious molars and premolars were used, in which the RDT was measured utilising digital periapical radiographs, cone-beam computed tomographic (CBCT) scanning, and Hirox stereomicroscopy (histological sections). The classification framework was constructed using the identified factors, and validated using the modified Delphi technique with the help of international experts in the field of caries management. A content analysis was conducted on the articles included for the SR, one-way ANOVA was applied to compare the RDT measurements obtained during the in vitro experiment, and a content validity index (CVI) was utilised to assess the consensus agreement among international experts participating in the modified Delphi process. A total of 17 articles were included in the SR after the full-text screening, upon which the content analysis was performed. Only 63 teeth were used in the in vitro experiment, that met the inclusion and exclusion criteria. No significant difference was observed in RDT values acquired using CBCT and Hirox. Nonetheless, a significant difference (p<0.05) was observed between digital radiographs and CBCT, as well as between digital radiographs and Hirox. A total of 10 components were identified from the SR/content analysis and in vitro experiment, that helped in constructing the Dentinal Triage framework. Next, this framework underwent validation utilising three rounds of modified Delphi with 22 international experts, yielding item-CVI scores of 0.89 (89%), 0.97 (97%), and 0.98 (98%), respectively; indicating a strong consensus agreement among the international expert panel in regards to the entire Dentinal Triage by the end of round three. In conclusion, it was observed that digital radiography overestimated RDT relative to CBCT and Hirox microscopy. Nevertheless, it still served as the most practical chairside tool for assessing coronal RDT. The novel coronal RDT classification, the Dentinal Triage, was developed and successfully validated with a 98% consensus agreement amongst the international dental experts in caries management.